DESIGNING THE STRATEGIES FOR SOCIO-ECONOMIC DEVELOPMENT OF MUNICIPALITY DISTRICTS ON THE BASIS OF SYNTHESIS METHODS FOR COMPLEX SYSTEMS RESEARCH - Sergey N. Isaev; Alexander V. Bykov; Galina V. Gorelova; Evgenij Yu. Zakharchenko; Anna V. Maslennikova; Svetlana A. Khlebnikova (Статистика и экономика, 2016)
The article presents the results of research work on designing the strategies for socio-economic development for the Sholokhovskiy municipal district of Rostov region and Chusovskoy municipal district of Perm Region, which was made by research team of autonomous nonprofit organization of higher education «Eurasian Open Institute» (EOI) during the 2012-2013.